The effect of an acute sleep hygiene strategy following a late-night soccer match on recovery of players. (27th May 2016) - Fullagar, Hugh; Skorski, Sabrina; Duffield, Rob; Meyer, Tim
ABSTRACT: Elite soccer players are at risk of reduced recovery following periods of sleep disruption, particularly following late-night matches. It remains unknown whether improving sleep quality or quantity in such scenarios can improve post-match recovery. Therefore, the aim of this study was to investigate the effect of an acute sleep hygiene strategy (SHS) on physical and perceptual recovery of players following a late-night soccer match. In a randomised cross-over design, two highly-trained amateur teams (20 players) played two late-night (20:45) friendly matches against each other seven days apart. Players completed an SHS after the match or proceeded with their normal post-game routine (NSHS). Over the ensuing 48 h, objective sleep parameters (sleep duration, onset latency, efficiency, wake episodes), countermovement jump (CMJ; height, force production), YoYo Intermittent Recovery test (YYIR2; distance, maximum heart rate, lactate), venous blood (creatine kinase, urea and c-reactive protein) and perceived recovery and stress markers were collected. Sleep duration was significantly greater in SHS compared to NSHS on match night ( P = 0.002, d = 1.50), with NSHS significantly less than baseline ( P < 0.001, d = 1.95). Significant greater wake episodes occurred on match night for SHS ( P = 0.04, d = 1.01), without significant differences between- or within-conditions for sleep onset latency ( P = 0.12), efficiency ( P = 0.39) or wake episode duration ( P = 0.07). No significant differences were observed between conditions for any physical performance or venous blood marker (all P > 0.05); although maximum heart rate during the YYIR2 was significantly higher in NSHS than SHS at 36 h post-match ( P = 0.01; d = 0.81). There were no significant differences between conditions for perceptual "overall recovery" ( P = 0.47) or "overall stress" ( P = 0.17). Overall, an acute SHS improved sleep quantity following a late-night soccer match; albeit without any improvement in physical performance, perceptual recovery or blood-borne markers of muscle damage and inflammation.